Disruptive Innovation in Aerospace and Defense in Indian MSME. Issue 2 (December 2019) - Rao, Shuktij Singh; Banik, Arindam; Khanna, Ashutosh; Philip, Deepu
Abstract: Various movements in the Indian aerospace and defense industry indicate that the forces of disruptive innovation have been set in motion by the Government of India with signals of change in the industry, thereby nudging it toward disruption. This case studies one such company from the micro, small and medium enterprise (MSME) sector in pursuit of disruptive innovation in the Indian aerospace and defense industry. This case introduces and explains in detail the factors of disruptive innovation in aerospace and defense industry. It gives an inside view of Indian MSME's environmental and internal situations in the Indian aerospace and defense industry and the problems faced by an entrepreneur who is looking for using technology to create disruption in industry.